Brody Olson: capstone - Olson, Brody, artist (Colorado State University. Libraries, 2019)
The artist's statement: Where you are now may be fine, but that doesn't mean it will always be that way. Nature is an unpredictable beast that can't be tamed, we must always be aware of what's yet to come. Dark clouds surround our planet, no matter where you live or what language you speak, nature will have an impact on you. People have always found a way to adapt to the storms and being able to find beauty and peace during the hard times is something magical in itself. I intend to show you how inspiring nature can be during times of rough weather. This work is based on different experiences and moments that I find myself in while venturing into the wild. I paint using my photographs and sketches to re-create these different journeys. Through the processes of painting, I am able to reminisce on times that are of value to me. I hope to give people a glimpse of what is still out there when you escape the busyness of life. If you venture into the wild, you may just find yourself surrounded by wonderful moments.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: painting